Estratégia e estrutura organizacional na indústria de alimentos: o caso Sadia - Sato, Geni Satiko (1998)
This study aims to be a theorethical contribution to the understanding of the relationship between organizationaI structures and strategies. A case study on Sadia, the leading company in the sector of industrialized meat in Brazil, was developed for this objective. It is worth noticing that as this is a unique and distinct case, the results must not be generalized. Sadia's organizational structure went through two great strategic changes throughout half a century of existence. The first took place in 1970, when the holding structure was adopted and stock issued to the publico This change was brought about by strategies focusing on its geographic expansion and the diversification from pork to poultry. The second change was in 1994, when a multidivisonal structure was chosen; by then, the company had already consolidated its leadership and directed its diversification towards industrialized products with aggregate value. Parallel to the structural changes, a suitable corporate model, ruling shareholders behavior, was another driving force behind its leadership. Other factors essential to success were both the cultural and humane aspects present in the organization such as the founder' s leadership and the emergente of new leaders in the ensuing generations.